Simultaneous fluoride and arsenic removal from groundwater by using aluminium sacrificial anode - Ihos Monica; Manea Florica; Pode Rodica; International Symposium on Analytical and Environmental Problems (22.) (2016) (Szeged) (2016)
The simultaneous removal of fluoride and arsenic in groundwater collected from three deep wells situated in Western part of Romania was carried out by electrocoagulation (EC) with aluminium sacrificial anode. The current density was of 156, 480 and 780 A/m2 , respectively and the electrolysis time 60 min. The removal efficiency of fluoride and arsenic was determined based on their residual concentration. Also, the specific energy consumption was calculated and it was in the range of 0.14 - 1.40 kWh/m3.